PENERAPAN MODEL FLIPPED CLASSROOM-STAD UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Arini Dwi Mayasari; Mohammad Budiyanto; Aris Rudi Purnomo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This study aimed to describe the increase in student cognitive learning outcomes by implementing flipped classroom-STAD models in the blood circulatory system material. This quantitative study was a pre-experimental design with one group pretest posttest as research design. Samples in this study were 32 students of VIII H class in SMPN 27 Surabaya. Data collection techniques used were test methods given before (pretest) and after (posttest) learning to measure student cognitive learning outcomes and a questionnaire methods to measure learning model implementation. Learning outcomes data were analyzed using paired t-test and N-Gain test. Paired t-test result indicated that there was an effect of treatment on student learning outcomes. As for the N-Gain test result obtained value of 62% that indicated an increase in medium category and classical completeness also achieved with a percentage of 87%. Based on the result, it can be concluded that the flipped classroom-STAD models implementation improved student learning outcomes on science learning in the blood circulatory system material.